Re-examining monetary and fiscal policy for the 21st century - Arestis, Philip; Sawyer, Malcolm C. (Cheltenham, UK : Edward Elgar, 2004)
This book provides a much-needed re-examination of monetary and fiscal policies, their application in the real world and their potential for macroeconomic policy in the 21st century. It provides a detailed discussion and critique of the 'new consensus' in macroeconomics along with the monetary and fiscal policies encapsulated within it. The authors argue that monetary policy is an ineffective means of controlling inflation and, if not used properly, can also have detrimental effects on the supply-side of the economy. They further contend that fiscal policy remains a potent instrument for influencing aggregate demand. Using detailed analysis the authors emphasise the role of capacity constraints as possible inflation barriers and argue against the NAIRU as a labour market phenomenon. The book concludes by critically examining the economic policies of the European Economic and Monetary Union.
Includes bibliographical references and index.
oif 16/07/2014
Loans
Keywords: Monetary policy; Fiscal policy; Inflation (Finance)